High‐Throughput Phenotypic Screening of Human Astrocytes to Identify Compounds That Protect Against Oxidative Stress. (31st March 2016) - Thorne, Natasha; Malik, Nasir; Shah, Sonia; Zhao, Jean; Class, Bradley; Aguisanda, Francis; Southall, Noel; Xia, Menghang; McKew, John C.; Rao, Mahendra; Zheng, Wei
Abstract : Using astrocytes differentiated from human embryonic stem cells, an assay was developed to identify compounds that protect against oxidative stress, a condition associated with many neurodegenerative diseases. The assay has been optimized for high‐throughput screening in a 1, 536‐well plate format. From a screen of approximately 4, 100 bioactive tool compounds and approved drugs, 22 were identified that acutely protect human astrocytes from the consequences of hydrogen peroxide‐induced oxidative stress. Abstract : Astrocytes are the predominant cell type in the nervous system and play a significant role in maintaining neuronal health and homeostasis. Recently, astrocyte dysfunction has been implicated in the pathogenesis of many neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. Astrocytes are thus an attractive new target for drug discovery for neurological disorders. Using astrocytes differentiated from human embryonic stem cells, we have developed an assay to identify compounds that protect against oxidative stress, a condition associated with many neurodegenerative diseases. This phenotypic oxidative stress assay has been optimized for high‐throughput screening in a 1, 536‐well plate format. From a screen of approximately 4, 100 bioactive tool compounds and approved drugs, we identified a set of 22 that acutely protect human astrocytes from the consequences of hydrogen peroxide‐induced oxidative stress. Nine of these compounds were also found to be protective of induced pluripotent stem cell‐differentiated astrocytes in a related assay. These compounds are thought to confer protection through hormesis, activating stress‐response pathways and preconditioning astrocytes to handle subsequent exposure to hydrogen peroxide. In fact, four of these compounds were found to activate the antioxidant response element/nuclear factor‐E2‐related factor 2 pathway, a protective pathway induced by toxic insults. Our results demonstrate the relevancy and utility of using astrocytes differentiated from human stem cells as a disease model for drug discovery and development. Significance: Astrocytes play a key role in neurological diseases. Drug discovery efforts that target astrocytes can identify novel therapeutics. Human astrocytes are difficult to obtain and thus are challenging to use for high‐throughput screening, which requires large numbers of cells. Using human embryonic stem cell‐derived astrocytes and an optimized astrocyte differentiation protocol, it was possible to screen approximately 4, 100 compounds in titration to identify 22 that are cytoprotective of astrocytes. This study is the largest‐scale high‐throughput screen conducted using human astrocytes, with a total of 17, 536 data points collected in the primary screen. The results demonstrate the relevancy and utility of using astrocytes differentiated from human stem cells as a disease model for drug discovery and development.